Risk of Respiratory Diseases with Use of Psychotropic Drugs: Results of a Community-based Cross-sectional Study from South India - Eby, Abhirami; Dang, Raman; Jacob, Elsa (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: The study evaluated the effect of various psychotropics on pulmonary function to identify the psychotropic drug class most commonly associated with risk of respiratory disorders. Since psychotropic medications have safety concerns for usage in general population, their use in people with Coronavirus Disease (COVID-19) is considered challenging. The study may also serve to draw evidence-based practical recommendations for the treatment of people with COVID-19. Materials and Methods: A 10-item containing questionnaire was designed to capture clinical information regarding psychotropic use and respiratory disorders. Internal consistency and reproducibility were determined using Cronbach’s alpha and intra-class correlation coefficient respectively. A validated questionnaire was administered to patients or caregivers at a community pharmacy setup and data was collected through electronic data capture. All captured data were summarized descriptively and statistically analyzed using R Studio 4.0. Results: Cronbach’s alpha and intra-class correlation coefficient values were found to be 0.92 and 0.85 respectively. In a sample of 198 patients, benzodiazepines were the commonly used medication (43.9%) followed by selective serotonin reuptake inhibitors (21.2%), anti-psychotics (15.1%), mood stabilizers (7.6%) and others (12.2%). A statistically significant association was observed between benzodiazepine, second-generation antipsychotics, and respiratory disorders (OR 1.56 [1.1 – 2.3, p<0.1]). However, the use of first-generation antipsychotics was found to be less associated with respiratory infections. Conclusion: Benzodiazepine and second-generation antipsychotics were found to be significantly associated with respiratory disorders. Hence patients on psychotropics should be monitored for respiratory symptoms and the choice of anti-psychotic medications should be on existing clinical evidence. The psychotropics which were found to be safer through the study can be chosen to improve the quality of psychiatric care in COVID-19 patients, also promoting an optimal management of psychiatric conditions without worsening the medical condition due to COVID-19.
Keywords: Psychotropic; Anti-psychotics; Respiratory disorder; Pneumonia; COVID-19